(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2024)
This research is motivated by the emergence of various models of Muslim women’s clothing today which do not pay attention to the materials used, there are clothes that are covered but still reveal the curves of the body and are transparent. Therefore, this research aims to see how the interpretation of the tafsir al-Misbah and the tafsir al-Qur’an al-’Azhim compare regarding women’s clothing according to the Qur’an. This research is library research with a descriptive-analytical qualitative method. In this research, the data collection method used is documentation. The documentation data collected is in the form of Al-Qur’an texts, scriptures, books, journals, articles and others. The data analysis technique used is the muqarran or comparison method. The results of this research state that the provisions for women’s clothing according to Quraish Shihab in the tafsir al-Misbah and Ibnu Kathir in the tafsir of the Qur’an al-’Azhim are that Muslim women must wear clothes that cover their private parts with clothes that are wide, loose and cover their chests. However, there are differences of opinion in understanding the hijab which is part of women’s clothing, Quraish Shihab said that the verse does not order Muslim women to wear the hijab, because when they wear it partially, it’s just that the way they wear it doesn’t support what this verse wants. Meanwhile, Ibnu Katsir said that the verse above commands Muslim women to wear their headscarves, because the headscarf is an obligation for Muslim women to be different from other women.